Evaluating the influence of nature connection and values on conservation attitudes at a tropical deforestation frontier - Katarzyna M. Mikołajczak; Jos Barlow; Alexander C. Lees; Christopher D. Ives; Micha Strack; Oriana Trindade de Almeida; Agnis C. Souza; Frazer Sinclair; Luke Parry (Conservation Biology, 2023)
Inner phenomena, such as personal motivations for pursuing sustainability, may be critical levers for improving conservation outcomes. Most conservation research and policies, however, focus on external phenomena (e.g., ecological change or economic processes). We explored the factors shaping 9 conservation attitudes toward forest and wildlife protection among colonist farmers around an Amazonian deforestation frontier. Our data comprised 241 face‐to‐face quantitative surveys, complemented with qualitative insights from open‐ended questionnaire responses and opportunistic semistructured interviews. To account for the full spectrum of possible inner motivations, we employed measures of nature connection (indicating biospheric motivation) and personal values organized around the traditionalism (traditionalist through to high openness to change) and universalism dimensions (egoistic through to altruistic motivations). We used averaged beta‐binomial generalized linear models to assess the role of external factors (socioeconomic, sociodemographic, and environmental) and personal (inner) motivations on the variation in attitudes. Each attitude was modeled separately. The relative importance of each predictor was judged by the proportion of models where it appeared as significant. Proconservation views were expressed by the majority (at least 65%) of the respondents in 7 out of the 9 attitude models. The most consistent predictors were emotional nature connection and personal values (significant in 4–6 out of 9 models), rather than external phenomena (significant in 0–5 models). However, the poorest farmers had lower scores on the agreement with prioritizing nature over development (𝛽 = –0.52, 95% CI: –0.96 to –0.07). Qualitative data also indicated that economic barriers hinder forest conservation on farms. These results suggest that biospheric, traditionalistic, and altruistic motivations promote people's proconservation attitudes, but nurturing these latent motivations is unlikely to improve conservation outcomes if material poverty remains unaddressed. Integrating the inner–outer perspective into conservation thinking and practical interventions could foster environmental stewardship and increase human well‐being.

Recent advances in the delivery and applications of nonviral CRISPR/Cas9 gene editing - Frazer Sinclair; Anjuman A. Begum; Charles C. Dai; Istvan Toth; Peter M. Moyle (Drug Delivery and Translational Research, 2023)

Foraging behaviour and diet of Brown boobies Sula leucogaster from Tinhosas Islands, Gulf of Guinea - Edna Correia; Paulo Catry; Frazer Sinclair; Yodiney dos Santos; Joana I. Robalo; Cristina S. Lima; José Pedro Granadeiro (Marine Biology, 2021)